A Systemic Approach to the Development of a Policy Mix for Material Resource Efficiency - Tomas Ekvall; Martin Hirschnitz-Garbers; Fabio Eboli; Aleksander Sniegocki (Fondazione Eni Enrico Mattei (FEEM), 2016)
Increasing material use efficiency is important to mitigate future supply risks and minimize environmental impacts associated with the production of the materials. The policy mix presented in this paper aims to reduce the use of virgin metals in the EU by 80% by 2050. We used a heuristic framework and a systems perspective for designing the policy mix that combines primary instruments (aimed to achieve the 80% reduction target – e.g. a materials tax, technical regulations and removal of environmentally harmful subsidies) and supportive instruments (aimed to reduce barriers to implementing the primary instruments and to contribute towards the policy objectives – e.g. research & development support, and advanced recycling centers). Furthermore, instruments were designed so as to increase political feasibility: e.g. taxes were gradually increased as part of a green fiscal reform, and border-tax adjustments were introduced to reduce impacts on competitiveness. However, even in such a policy mix design ongoing ex-ante assessments indicate that the policy mix will be politically difficult to implement – and also fall short of achieving the 80% reduction target. Nonetheless, we suggest combining primary and supportive instruments into coherent and dynamic policy mixes as a promising step towards system reconfigurations for sustainability.
Keywords: L72; Q32; 330; Policy Mix; Policy Development; Resource Efficiency; Material Efficiency; Recycling; European Union; Sensitivity Model